Urban religion beyond the city: theory and practice of a specific constellation of religious geography-making. Issue 2 (3rd April 2023) - Rüpke, Jörg; Urciuoli, Emiliano Rubens
ABSTRACT: The concept of urban religion demands us to start operationally with analyzing characteristics of urban environments and their impact on religious forms of communication. Yet this notion was not necessarily designed to apply only to the city and related phenomena exclusively observed in city spaces. Practices, beliefs, even institutions developing as urban religion spread out beyond the city. Thus, the geography of lived urban religion and of agents of urbanity is different from what the same people imagine and geographically locate as city space. This article intends to develop the conceptual tools for analyzing this blurring of boundaries produced by religious semantics, discourses and practices interacting with implicit and explicit border-constructions linked to practices of 'urbanity'. The highly debated 'urban' or 'anti-urban' character of ancient Christianities serves as our point of departure for developing comparative tools.